Histological characterization of sexual reproduction in the coral Pocillopora damicornis (Coelenterata: Scleractinia) from the Red Sea - Yahya AM Floos (Open Journal of Biological Sciences - Peertechz Publications, 2022)
The scleractinian coral is common along the Red Sea coast, and its reproductive mode and period of reproduction were assessed using histological preparations. the sexuality, and reproductive mod timing of reproductive of pocillopora damicornis from adjacent to the fringing reefs of the Ubhur Creek in the Red Sea, were assessed using a serial histological section. Sexual reproduction in pocillopora damicornis a shallow water hermatypic coral was studied from December 2011 to November 2012. pocillopora damicornis is a simultaneous hermaphrodite with ovary and testis in the project into the body cavity on the same mesentery. Sperm and eggs were usually released simultaneously from the same polyp. The onset of the reproductive period of pocillopora damicornis was found to be limited (April to May). In the number of eggs and testes observed in this period, the gonads were found in the polyps. The pocillopora damicornis egg size ranged from 49.80 µm (in March) to 125.0 µm (in May). Four stages were chosen, to reflect very immature ovaries, the early stages of oocyte development, ova near maturity, and mature ova, and also four distinct stages of sperm development were identified. The state of gonads development (eg. testis and eggs) was measured by a calibrated eyepiece micrometer of a compound light microscope. Zooxanthellae were presented in the mature oocytes in pocillopora damicornis. This study aimed to examine the reproduction mode and timing of pocillopora damicornis.